2014
DOI: 10.1542/peds.2014-0316
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Certification Part 4 Credit and Recruitment for Practice-Based Research

Abstract: BACKGROUND: Competing priorities in pediatric practice have created challenges for practice-based research. To increase recruitment success, researchers must design studies that provide added value to participants. This study evaluates recruitment of pediatricians into a study, before and after the development and addition of a quality improvement (QI) curriculum approved for American Board of Pediatrics Maintenance of Certification (MOC) Part 4 Credit as an enrollment incentive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Our findings that behavioral problems were associated with lower developmental scores were consistent with those found in the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B) [13] that followed 8,000 children born term and preterm. The ECLS-B study found that those children with cognitive delay at 9 and 24 months (defined by scores on the Bayley Short Form) had significantly more behavioral problems by 4 and 5 years, with SES associated with worse behavior problems.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings that behavioral problems were associated with lower developmental scores were consistent with those found in the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B) [13] that followed 8,000 children born term and preterm. The ECLS-B study found that those children with cognitive delay at 9 and 24 months (defined by scores on the Bayley Short Form) had significantly more behavioral problems by 4 and 5 years, with SES associated with worse behavior problems.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that offering MOC credit can increase participation for QI projects in community settings. 29 MOC was established by the American Board of Medical Specialties to encourage ongoing improvement in physicians' knowledge, and improvement in medical practice to evidencebased care. 30 In part IV of the MOC requirements, physicians participate in approved QI projects.…”
Section: Discussionmentioning
confidence: 99%
“…30 In part IV of the MOC requirements, physicians participate in approved QI projects. 29 However, MOC requirements have been criticized because they do not always fulfill practice-specific needs, and they provide minimal benefit if not tailored to the practice of the physician, 30 and so valuable MOC projects are needed. 31 We demonstrate that regional children's hospitals can use MOC requirements to help community hospitals adopt evidence-based best practices and improve important outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, demands for increased efficiency in office practice dictated by such factors as payment pressures and increased patient complexity have reduced time for practitioner involvement in research. 17 Combined, these trends pose the question: What are the challenges and efficiencies related to implementing an effective, minimally demanding practice-based intervention in a fully electronic environment, as compared with the environment in years past?…”
Section: Introductionmentioning
confidence: 99%